2018
DOI: 10.1002/smll.201802112
|View full text |Cite
|
Sign up to set email alerts
|

Improving Drug Delivery of Micellar Paclitaxel against Non‐Small Cell Lung Cancer by Coloading Itraconazole as a Micelle Stabilizer and a Tumor Vascular Manipulator

Abstract: Although polymeric micelles of paclitaxel (PTX) significantly reduce excipient‐induced toxicity compared with Taxol, they exhibit few clinical advantages in tumor inhibition and overall survival. To improve, itraconazole (ITA), an antifungal drug with potent anti‐angiogenesis activity, is co‐encapsulated together with PTX within the PEG‐PLA micelles. The strong intermolecular interactions between the payloads inhibit drug crystallization and prevent drugs from binding with external proteins, render super‐stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…This was not examined in detail in this work, but the anti‐tumor results show that any co‐loader impact on anti‐tumor efficacy was modest. This is not always the case, and one of the co‐loaders examined, itraconazole, was shown to enhance efficacy when co‐formulated with PTX and stabilize micelles . In general, benign and inert co‐loaders that are generally recognized as safe (which CLT and MIF are not) would avoid safety concerns and simplify data interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…This was not examined in detail in this work, but the anti‐tumor results show that any co‐loader impact on anti‐tumor efficacy was modest. This is not always the case, and one of the co‐loaders examined, itraconazole, was shown to enhance efficacy when co‐formulated with PTX and stabilize micelles . In general, benign and inert co‐loaders that are generally recognized as safe (which CLT and MIF are not) would avoid safety concerns and simplify data interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…[28] The morphology of micelles was characterized by transmission electron microscopy (FEI Tecnai Spirit Bio TWIN TEM D1297, USA) with negative staining with phosphotungstic acid. [28] The morphology of micelles was characterized by transmission electron microscopy (FEI Tecnai Spirit Bio TWIN TEM D1297, USA) with negative staining with phosphotungstic acid.…”
Section: Methodsmentioning
confidence: 99%
“…[14] Therefore, small molecular inhibitors of Hh, including cyclopamine, arsenic trioxide, [15] vismodegib www.advancedsciencenews.com www.advtherap.com (GDC-0449, Genentech), [16,17] NVPLDE225 (Novartis), [18] IPI-926 (Infinity), [19] and XL-139 (BMS/Exelixis), [20] were exploited to disrupt the Hh-inducing microenvironment, in which GDC-0449 was approved as a first-line therapy for advanced unresectable basal cell carcinoma. [21,[25][26][27] In a previous study, [28] we developed a PTX and ITA co-encapsulated poly (ethylene glycol)-b-poly (d,l-lactide) (PEG-PLA) micelle, termed as "PIM," and has demonstrated remarkably superior efficacy in inhibiting tumor growth, preventing recurrence, and reversing PTX resistance in a variety of clinically relevant NSCLC models. Nevertheless, reprogramming of the stroma by inhibition of the Hh signaling pathway combined with chemotherapy drug has been considered as a useful therapeutic strategy to evaluate for PDAC therapy, [16,[22][23][24] and the previous preclinical study showed that the Hh inhibitors combined with chemotherapy showed prolonged survival compared to GEM monotherapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations